THE ETHICAL DIMENSIONS OF ARTIFICIAL INTELLIGENCE IN EDUCATION: A PHILOSOPHICAL AND LITERARY FUSION OF TECHNOLOGY AND HUMAN GUIDANCE - Yiwen Guo (Journal of Dharma, 2024)
The technological advancements of the modern era have significantly benefited the global community, fostering a collaborative society aimed at promoting the well-being of the world. While some view Artificial Intelligence (AI) as an autonomous challenge or a potential threat to future generations, capable of controlling everything, this work presents an alternative perspective, highlighting AI as a privilege that addresses critical issues from a global citizen’s standpoint. The study further explores the philosophical implications of AI within the educational sphere while emphasizing the importance of a collaborative approach to tackling global challenges, particularly in higher education, where AI tools and techniques are leveraged to promote a more just world. This research also highlights the concept of literary preservation in digital formats, ensuring accessibility for future generations. In doing so, it delves into the ethical dimensions of AI in education, particularly from the perspective of community building. Furthermore, it critiques the misuse of AI, especially when Assistive Technology (AT) is replaced by more dominant, ruling technologies. The research argues that machines themselves are not inherently harmful; rather, it is their misuse for destructive purposes that leads to negative consequences. Hence, the author proposes innovative methods to challenge and reshape the current discourse surrounding AI and its impact on society.